Corporate Governance sebagai Variabel Moderating dengan Net Working Capital, Capital Expenditure, Cash Conversion Cycle, Cash Flow, dan Growth Opportunity yang Dapat Mempengaruhi Cash Holding - Nur Hayati (Business Management Analysis Journal (BMAJ), 2020)
This research is intended to analyze net working capital, capital expenditure, cash conversion cycle, cash flow and growth opportunity towards cash holding with the activity of the board of commissioners as a moderating variable. The population of this research is all consumer goods industry companies listed on the Indonesia Stock Exchange in 2014-2018. The sample of this research is 30 companies determined by purposive sampling technique. The data analysis technique used in this study is multiple linear regression analysis using WarpPLS 6.0 software. The results show that net working capital, capital expenditure dan growth opportunity have no signifikan relationship on cash holding. Meanwhile, cash conversion cycle and cash flow have significant relationship on cash holding. The result of shows that the activity of the board of commissioners can moderate between cash conversion cycle and cash flow on cash holding. It is suggested that future studies use other models, apart from multiple linear regression and increase the sample of companies.Penelitian ini bertujuan untuk menganalisis net working capital, capital expenditure, cash conversion cycle, cash flow dan growth opportunity terhadap cash holding dengan aktivitas dewan komisaris sebagai variabel moderating. Populasi penelitian ini seluruh perusahaan industri barang konsumsi yang terdaftar pada Bursa Efek Indonesia periode 2014-2018. Sampel penelitian ini sebanyak 30 perusahaan yang diambil dengan teknik purposive sampling. Teknik analisis data yang digunakan pada penelitian ini adalah analisis regresi linear berganda dengan menggunakan software WarpPLS 6.0. Hasil analisis menunjukkan bahwa variabel net working capital, capital expenditure dan growth opportunity tidak berpengaruh signifikan terhadap cash holding. Sedangkan, variabel cash conversion cycle dan cash flow berpengaruh signifikan terhadap cash holding. Hasil penelitian juga menunjukkan aktivitas dewan komisaris dapat memoderasi variabel cash conversion cycle dan cash flow terhadap cash holding. Disarankan penelitian yang akan datang menggunakan model lain, selain regresi linear berganda dan menambah sampel.